Advanced modular system in data acquisition for muon lifetime measurements of cosmic ray muon - Reserva, Rosario L.; Bacala, Angelina M. (2000)
Muons are created in the upper atmosphere when highly energetic cosmic ray primaries of extra-terrestrial origin collide with the atmosphere's molecules. Cosmic ray muons decay via weak interaction with particles of absorbing matter producing an electron and a partner neutrino in the process. At MSU-IIT's high-energy physics laboratory, five different materials absorbers were used to capture a decaying muon: lead, aluminum, wood, copper and iron. The muon decay life-time is measured by timing the observation of a signal from an incoming muon and its decay electron in the absorber using an assembly of high-precision scintillation detectors and advanced electronic modular systems of nanosecond accuracy. Analog pulses generated by the scintillator detectors are directed using co-axial signal cables into several nuclear instrumentation modules (NIM) such as the discriminators, coincidence module and gate generator that eliminate noise and ensure purity of desired muon signals. The NIM output digital signals which then go into the input channel of a time-to-digital converter module or the TDC.